Network Forensic: Analysis of Client Attack and Quality of Service Measurement by ARP Poisoning using Network Forensic Generic Process (NFGP) Model - Ramadhan, Rizdqi Akbar; Tira, Agro Tambas; Fadhilah, M. Rizki (Sistemasi: Jurnal Sistem Informasi, 2024)
In computer network, communication from one computer to another computer can be intercepted, the way to intercept communication between network devices is with Address Resolution Protocol Poisoning attack. This attack can steal data such as usernames and passwords, modify traffic, and stop the traffic itself. This research implements the Network Forensic Generic Process model as a reference in Network Forensics practice. Apart from that, this research also measures quality of service to compare parameters before the attack and when the attack occurred. The tools used in this research are Wireshark, XArp, and Snort. This research succeeded in obtaining authentic information from the evidence obtained. The results of quality of service measurements showed that the quality of service parameters changed when the attack occurred. This research can be a reference in improving network security by better understanding the threats that may be encountered and providing valuable insight for future security prevention and response efforts.